New aspects for match analysis to improve understanding of game scenario and training organization in top-level male water polo players - Melchiorri, G.; Viero, V.; Bianchi, D.; Tancredi, V.; Bonifazi, M.; Campagna, A.; Triossi, T. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: We intended to verify through time-motion analysis the characteristics of the sequences of actions in terms of occurrence during water polo matches: number, duration, and possible relationships with technical-tactical aspects. METHODS: Water polo matches played at the 18th FINA World Championships 2019, Gwangju, South Korea, were chosen for examination, and the analysis involved both single actions and Trains of Actions (ToAs). A ToA is a sequence of actions that occurs during the match without actual game interruption. RESULTS: A total of 1261 game actions were evaluated in the 17 matches analyzed. In 89% of cases the actions occurred in ToAs while in 11% of cases they took place as single actions. On average, each match included 74.4±5.3 actions; of these, only 7.9±3.4 (CI at 95%: lower bound 6.1 and upper bound 9.6) were single actions while 66.2±5.5 occurred in sequences (ToA2=29.6±9.0%; ToA3=26.1±9.7%; ToA4=16.5±10.6%). The winning team performed on average more actions than the losing one (42.1±6.1 vs. 32.0±6.4; effect size: 1.67; P value: 0.001). The ToAs had different compositions, from 2 to 18 actions, and then very different durations, from about 1 minute up to 8 minutes. 66% of goals were scored after ToAs and 34% after single actions. CONCLUSIONS: The study of ToAs provides useful information on the physiological demand of the game, which may help to plan and organize physical training making it as specific as possible. The description of ToAs can help coaches to better define the game scenario and understand which technical and tactical measures are needed to improve game organization.